1985
DOI: 10.1152/jappl.1985.59.5.1394
|View full text |Cite
|
Sign up to set email alerts
|

Thermoregulatory and blood responses during exercise at graded hypohydration levels

Abstract: We studied the effects of graded hypohydration levels on thermoregulatory and blood responses during exercise in the heat. Eight heat-acclimated male subjects attempted four heat-stress tests (HSTs). One HST was attempted during euhydration, and three HSTs were attempted while the subjects were hypohydrated by 3, 5, and 7% of their body weight. Hypohydration was achieved by an exercise-heat regimen on the day prior to each HST. After 30 min of rest in a 20 degrees C antechamber the HST consisted of a 140-min e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
226
4
4

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 321 publications
(246 citation statements)
references
References 0 publications
12
226
4
4
Order By: Relevance
“…During sauna bathing, sweating begins quickly and reaches peak levels after approximately 15 minutes, with an average total secretion of 0.5 kg [15]. The magnitude of core temperature elevation ranges from 0.1 to 0.25 o C for every percent of BML [28,39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During sauna bathing, sweating begins quickly and reaches peak levels after approximately 15 minutes, with an average total secretion of 0.5 kg [15]. The magnitude of core temperature elevation ranges from 0.1 to 0.25 o C for every percent of BML [28,39].…”
Section: Discussionmentioning
confidence: 99%
“…Body water loss of 2% can reduce work capacity by 20%. Marked dehydration (5% BWL) reduces threshold and slope responses for sweating [29,39]. Dehydration in excess of 5% BWL can have serious health implications, and BWL higher than 8-10% has lethal consequences [35].…”
Section: Discussionmentioning
confidence: 99%
“…Severe dehydration may increase the risk of heat-related illnesses, by impairing thermoregulation and augmenting thermal (Sawka et al 1985) and cardiovascular (Montain and Coyle 1992) strain, leading to a decrease in exercise-heat tolerance (Cheung and McLellan 1998a;Sawka et al 1992). Workers and medical personnel should, however, be alerted to the potential dangers of exercise-associated hyponatremia due to overdrinking during exercise in hot and humid environments (Lee et al 2011).…”
Section: Heat Mitigation Strategiesmentioning
confidence: 99%
“…6 Gonzalez-Alonso et al 7 observed an additive effect from hypohydration and heat on increasing cardiovascular strain when performing submaximal exercise. Unfortunately, inconsistent results that can be explained from the choice and subsequent interpretation of methodological designs has led to a poor understanding of the relationship between hypohydration and anaerobic performance.…”
mentioning
confidence: 99%